HUBUNGAN DUKUNGAN KELUARGA DENGAN KONSEP DIRI PADA PASIEN REMAJA YANG MENERIMA KEMOTERAPI DI RSUD DR SAIFUL ANWAR MALANG - Reza Andi Adma Wijaya; Reny Tri Febriani; Puguh Raharjo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Cancer can attack anyone, including teenagers. Cancer treatment in adolescents will go through a series of chemotherapy treatment processes. Adolescent patients who receive chemotherapy are at risk of experiencing side effects both physically and psychologically which are feared to affect their self-concept. One thing that influences teenagers' self-concept is family support. The design of this research is an observational analytical method with a cross sectional approach which aims to analyze the relationship between two variables at one time, namely the relationship between family support and self-concept in adolescents receiving chemotherapy. The sampling technique used was total sampling, namely all teenage patients who received chemotherapy at RSUD Dr Saiful Anwar, Malang as the sample. The research instruments were a family support questionnaire and a self-concept questionnaire which were filled in by adolescent patients. The research results showed that the majority of teenage patient respondents received high family support, namely 37 respondents (66.1%), and it was found that almost all respondents had a high self-concept, namely 50 respondents (89.3%). Based on the Pearson statistical test, it shows an r value of 0.608 (p value <0.05), so the results of this research show that there is a positive and strong relationship, the higher the family support, the higher the patient's self-concept. Therefore, families must be involved in providing support during chemotherapy with the hope that teenagers' self-concept will improve, they will have high self-confidence so that it will also have a positive impact during treatment.